Cerai Susuk di Kabupaten Banyuwangi - Lilit Biati (Proceedings of Annual Conference for Muslim Scholars, 2018)
For life in the land actually is the last alternative for a person, except around his place there are no job opportunities. Therefore berburuh to another country is a great alternative employment opportunities primarily due to its natural condition. The purpose of this study to describe the process of divorce implant is mostly done by maids against their husbands in Banyuwangi. As well as assess the impact of migrant maids to the harmony of households. Hence, this study was conducted using research methods to uncover a phenomenon qualitatively divorce implant that is currently rampant in Banyuwangi. The data collection technique using participant observation, interview and documentation. data reduction, data presentation and conclusion. From some research findings concluded that there are factors which then triggers that cause divorce implants (the husband's income is low, the husband does not work, cheating, defamation victim, meddling parents, reluctant to return to their homeland and the rupture of communication). While the process of (KHI) Article 132 paragraph and gender studies in fact women (wives) are justified to help the family economy, but the independence of wives would trigger gender awareness high and a cause for divorce implant that is getting phenomenal in Banyuwangi